BRCC3 Promotes Tumorigenesis of Bladder Cancer by Activating the NF-κB Signaling Pathway Through Targeting TRAF2 - Tao, Huangheng; Liao, Yixiang; Yan, Youji; He, Zhiwen; Zhou, Jiajie; Wang, Xinghuan; Peng, Jianping; Li, Shangze; Liu, Tao (Frontiers in Cell and Developmental Biology, 2021)
NF-κB signaling is very important in cancers. However, the role of BRCC3-associated NF-κB signaling activation in bladder cancer remains to be characterized. Western blotting and IHC of tissue microarray were used to confirm the abnormal expression of BRCC3 in bladder cancer. Growth curve, colony formation, soft agar assay and Xenograft model were performed to identify the role of BRCC3 over-expression or knock-out in bladder cancer. Further, RNA-Seq and luciferase reporter assays were used to identify the down-stream signaling pathway. Finally, co-immunoprecipitation and fluorescence confocal assay were performed to verify the precise target of BRCC3. Here, we found that high expression of BRCC3 promoted tumorigenesis through targeting the TRAF2 protein. BRCC3 expression is up-regulated in bladder cancer patients which indicates a negative prognosis. By in vitro and in vivo assays, we found genetic BRCC3 ablation markedly blocks proliferation, viability and migration of bladder cancer cells. Mechanistically, RNA-Seq analysis shows that NF-κB signaling is down-regulated in BRCC3-deficient cells. BRCC3 binds to and synergizes with TRAF2 to activate NF-κB signaling. Our results indicate that high BRCC3 expression activates NF-κB signaling by targeting TRAF2 for activation, which in turn facilitates tumorigenesis in bladder cancer. This finding points to BRCC3 as a potential target in bladder cancer patients.